Determinants of Credit Default Among Generation Z Paylater Users in Pangkal Pinang City, Indonesia - Adinda Okta Olivia; Nizwan Zukhri; Darman Saputra (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the influence of financial literacy, individual income, and ease of access on credit default among Generation Z paylater users in Pangkal Pinang City. Research Method: A quantitative associative approach was employed using data from 122 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS 25. Results and Discussion: The results show that financial literacy and ease of access have a significant negative effect on credit default. In contrast, individual income does not have a significant effect. Simultaneously, all variables significantly influence credit default, explaining 15.6% of the variance. These findings indicate that credit default behavior is associated with financial understanding and accessibility factors, although the explanatory power of these factors remains limited. Implications: The findings provide indicative insights to help financial service providers and regulators enhance transparency and support financial education on digital credit usage. Future research is recommended to include behavioral and contextual variables. Originality: This study contributes to the BNPL credit risk literature by providing empirical evidence from a local Indonesian context and highlighting behavioral and accessibility dimensions among Generation Z users.